Congenital Aplasia Cutis. A Series of Three Cases - Elsy Roxana Geroy Moya; María Elena Quiñones Hernández; Ángel Serafín Camacho Gómez (Revista Finlay)
Congenital aplasia cutis is a rare and heterogeneous disorder, with an estimated incidence of 1-3 cases per 10,000 births. It can appear in isolation or as part of several polymalformative syndromes, observing autosomal recessive and autosomal dominant inheritance patterns. Its treatment is controversial and will depend on the size, location, degree of involvement of the underlying structures and risk of potentially fatal complications. Three cases are presented with a diagnosis of congenital aplasia cutis, with different degrees of affectation, whose healing occurred in utero. A bibliographic review was carried out regarding the presentation of three clinical cases, the first 2 with a congenital aplasia cutis without associated malformation and the third with a bone defect and other associated malformations. This series of cases is presented due to the rare and heterogeneous nature of this condition.